Impact of Seasonal Variation on The Spermatozoa Reproductive Cycle of Hemantura Walgo (Müller & Henle, 1841) From Iraqi Marine Waters - Nasir, Noori AbdulNabi; Jasem, Janan Hasen (Iraqi Journal of Science, 2019)
The impact of seasonal variation on the spermatozoa reproductive cycle of Hemantura walgo in Western North of Arabian Gulf from January 2016 to December 2017 was studied. A total 225 individuals males of H. walga were collected using beach net. Gonads Somatic index (GSI) was high during May (10.1) and September (9.98) and the lowest values were recorded during on February, July and October with their values were 0.85, 1.21 and 1.43 respectively. Mature males were noticed during May and September which indicates there are two reproduction periods for H. walga during the year. The relationship between weight and width desk of H. walga was also investigated and generally demonstrated positive allometric growth (b > 3) for this species Thus, this study supplies to a better understand of seasonal variation on the spermatozoa reproductive cycle of H. walgo. The findings of this study also are essential to the estimation, protection and management of H. walgo , in addition to providing plan for the improvement of conservation strategies